Seismic Deformation Analysis of Rockfill Dam - Shakya, Yuman; Suwal, Rajan (Journal of the Institute of Engineering, 2014)
Core-shell interface is the interface between the core and the fill of the rockfill dam where due to the non-homogeneity of material there is the most likely slippage to occur. This slippage is modeled using ANSYS 10 with contact elements. Among the various parameters in the slippage phenomenon the material non-homogeneity and coefficient of friction is considered in the analysis. Analysis performed is free vibration and initial static deformation. The result from this analysis is then used as input in the time history analysis using Wilson-θ method performed in SAP 14. Then Newmark’s chart is used to find the settlement of the dam which is considered as the permanent settlement. The added mass of water for the time history model at reservoir full condition is calculated using Westerguaard’s Added Mass formulation. DOI: http://dx.doi.org/10.3126/jie.v10i1.10901 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014, pp. 199–204